Evaluation of motivational goals orientation in soccer - Hirota, Vinicius Barroso (2013)
This study aimed to evaluate and compare the motivational goals orientation of taskand ego for students belonging to two distinct environments sports football, a PrivateSchool of Sport and Non-Governmental Organization (ONG), both located in the city ofOsasco - SP. Through a descriptive research we applied a scale TEOSQ to a sample of196 subjects of both sexes aged between 7 and 17 years (mean 11.16 +2.09) and thedata were treated with the calculation of Alpha´s coefficient, mean, standard deviation,median, and the averages compared with the Mann-Whitney test. The results showedstability in the instrument with alpha of 0.78 and 0.68 for the task of self in school´ssport with an average of 4.28 of task and 2.40 of ego, since the ONG´s Alpha taskwas 0.74 and 0.60 of Alpha´s ego with an average of task and ego of 4.40 and 2.75respectively. We conclude the tendency for task-oriented with students predisposed toovereat constantly, and reliability of the instrument.